2018
DOI: 10.1111/mec.14898
|View full text |Cite
|
Sign up to set email alerts
|

Rapid establishment of a flowering cline in Medicago polymorpha after invasion of North America

Abstract: To establish and spread in a new location, an invasive species must be able to carry out its life cycle in novel environmental conditions. A key trait underlying fitness is the shift from vegetative to reproductive growth through floral development. In this study, we used a common garden experiment and genotyping‐by‐sequencing to test whether the latitudinal flowering cline of the North American invasive plant Medicago polymorpha was translocated from its European native range through multiple introductions, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 114 publications
(171 reference statements)
2
23
0
Order By: Relevance
“…Observed large variability within available germplasm could be used by breeders to select parental accessions for HV improvement breeding program that maximizes the winterspring biomass with low PY for cover crops (Wilke and Snapp, 2008;Wayman et al, 2016), or with high PY for´ley farmingś ystems (Loi et al, 2005;Renzi et al, 2017;Renzi et al, 2018). No significant correspondence was found between the geographic distance matrix and the phenotypic distance matrix (P > 0.15) among the naturalized AR populations and these results differ from Medicago polymorpha L., in which a correspondence between collection site and phenotypic traits (Loi et al, 1993;Helliwell et al, 2018) was observed.…”
Section: Phenotypic Variabilitymentioning
confidence: 88%
“…Observed large variability within available germplasm could be used by breeders to select parental accessions for HV improvement breeding program that maximizes the winterspring biomass with low PY for cover crops (Wilke and Snapp, 2008;Wayman et al, 2016), or with high PY for´ley farmingś ystems (Loi et al, 2005;Renzi et al, 2017;Renzi et al, 2018). No significant correspondence was found between the geographic distance matrix and the phenotypic distance matrix (P > 0.15) among the naturalized AR populations and these results differ from Medicago polymorpha L., in which a correspondence between collection site and phenotypic traits (Loi et al, 1993;Helliwell et al, 2018) was observed.…”
Section: Phenotypic Variabilitymentioning
confidence: 88%
“…It is also common for populations of temperate plants and ectotherms along latitudinal and altitudinal gradients to vary in responses to phenological cues [60], with strong selection on loci contributing to divergence in phenological timing [61] and rapid establishment of latitudinal clines in phenology in introduced species [62]. A recent common garden experiment transplanted replicate genotypes of the riparian tree Poplus fremontii across 58 of latitude, demonstrating that populations varied in their phenological plasticity and had substantial within-population G Â E [63].…”
Section: Population Comparisonsmentioning
confidence: 99%
“…Any of these processes would yield a pattern similar to enemy release but achieved through evolutionary processes. Our results suggest that novel genotypes, particularly those from regions above southern Portugal (Helliwell et al, 2018), attempting to colonize would have their establishment hampered compared to already present M. polymorpha. We did not compare herbivory in wild populations under natural field conditions and thus are not making inferences about the impact of herbivory on traits in each range.…”
Section: Discussionmentioning
confidence: 80%
“…This hierarchical sampling accounts for range, between-population, and within-population genetic variation and is captured in the mixed models we used for analysis. The study by Helliwell et al (2018) based on a novel, expanded collection that was not available to us showed that M. polymorpha variation is highest at the population level and lowest at the range level and found evidence supporting rapid evolution for flowering time in the invaded region. Future work leveraging genetic and genomic tools could partition how much of the change in plant-herbivore interactions is due to adaptation through natural selection versus genetic drift (Agrawal et al, 2015;Keller & Taylor, 2008;Schrieber et al, 2017).…”
Section: Discussionmentioning
confidence: 93%